Clinical Implications of the Progression‐Free Survival Endpoint for Treatment of Hormone Receptor‐Positive Advanced Breast Cancer. (2nd June 2016) - Kaklamani, Virginia G.
Abstract : Hormonal therapy for advanced breast cancer (ABC) has evolved significantly since the introduction of tamoxifen more than 40 years ago. The availability of selective antiestrogen therapies has further improved treatment options for women with hormone receptor‐positive (HR+) ABC. However, with the development of resistance to hormonal therapies, a new treatment paradigm has emerged based on our understanding of biological pathways involved in HR+ breast cancer and mechanisms of resistance to hormonal therapy. Recent drug development efforts have focused on combining hormonal treatment with agents that target mammalian target of rapamycin serine‐threonine kinases and cyclin‐dependent kinases. In parallel with the evolution of hormonal and targeted therapies, our understanding of the utility of clinical endpoints has deepened. Progression‐free survival (PFS) is a primary endpoint well‐understood by clinicians and is increasingly accepted as a surrogate for overall survival (OS) by the U.S. Food and Drug Administration. Yet the perceived clinical benefit of PFS to patients is less well understood. Patients may not grasp the implications of prolonged PFS, highlighting the reality that patient preference in treatment selection encompasses factors that extend beyond drug activity. This presents an opportunity for clinicians to discuss PFS with patients in the context of their treatment plans, clinical outcomes, and quality‐of‐life measures. The objective of this review is to explore the clinical validity of the PFS and OS endpoints and the clinical relevance of PFS and OS to patients, especially in light of drivers that led to a range of treatment options for patients with HR+ ABC. Abstract : This review explores drivers that led to advances in treatment options, the validity of progression‐free survival (PFS) and overall survival (OS) endpoints in clinical studies, and the clinical relevance of PFS and OS to patients with hormone receptor‐positive advanced breast cancer.